Introduction to the special issue on languages other than English: A reality check and a glimmer of hope - Thompson, Amy S. (Studies in Second Language Learning and Teaching, 2024)
The role of languages other than English (LOTEs) in K-16 education is rife with controversy, particularly in Anglophone contexts. In a recent edited volume, Lanvers et al. (2021) tackled this controversy head-on by creating an anthology that not only described the “language learning problems in Anglophone countries in a holistic and universal manner” (p. 8), but also offered “solutions and examples of positive, forward-thinking practice” (p. 8). Certainly, with the rise of Global English, and even more recently, with the sudden proliferation of AI-enhanced communication strategies, languages other than English are being further marginalized. This marginalization often comes in the form of extreme budget cuts and elimination of courses and programs, as is being seen in a variety of Anglophone contexts and is particularly salient in the US context (Kingson, 2023).